Do stress, depression, and anxiety lead to beliefs in conspiracy theories? - Fox N; Williams M; Hill S (SAGE Publications, 2025)
Previous research has found positive correlations between manifestations of psychological distress, such as anxiety, depression, and stress, and belief in conspiracy theories. However, it remains unclear whether these relationships represent causal effects. We therefore tested whether anxiety, depression, and stress affect (and are affected by) belief in conspiracy theories in a preregistered longitudinal study. We sampled participants from Australia, New Zealand, and the United Kingdom (N = 970) in seven monthly waves (October 2022–March 2023). Using multiple-indicator random-intercept cross-lagged panel models, we found support for only one of 15 preregistered hypotheses: a small cross-lagged effect of anxiety on belief in conspiracy theories. We also found no evidence of belief in conspiracy theories itself provoking psychological distress. Our findings provide grounds for skepticism of the notion that beliefs in conspiracy theories are often motivated by psychological distress or feelings of “existential threat.”